In Search of Creative EFL Teachers: A Perspective of Best Classroom Practices - Tono Suwartono; Nina Fivi Oktavia (Ahmad Dahlan Journal of English Studies, 2019)
Teaching is to create environment for students to learn. However, there are classrooms in which the students only sit and listen to the teacher. They are required to memorize words and grammar rules and the learners become reluctant and not motivated to learn. Therefore, creative teachers with certain qualities are needed to cope with this problem. This paper discusses a few important aspects of creative EFL teaching, delivers examples of classroom practices, and shares personal views related with the topic, notably the idea of creativity in ELT, in light of the author’s own teaching experience, research career and teacher training, as well as workshop-tours. It gives purposeful teaching techniques, ideas of how to create interesting classroom activities and how to use authentic material and resources, also how to optimize effective teaching aids /media.